BEST Life—"Bringing ECMO Simulation To Life"—How Medical Simulation Improved a Regional ECMO Program. Issue 11 (16th October 2018) - Puślecki, Mateusz; Ligowski, Marcin; Dąbrowski, Marek; Stefaniak, Sebastian; Ładzińska, Małgorzata; Ładziński, Piotr; Pawlak, Aleksander; Zieliński, Marcin; Dąbrowska, Agata; Artyńska, Aniela; Gezela, Mariusz; Sobczyński, Paweł; et al.
Abstract: The implemented "ECMO for Greater Poland" program takes full advantage of the ECMO (extracorporeal membrane oxygenation) perfusion therapy to promote health for 3.5 million inhabitants in the region. The predominant subjects of implementation are patients with hypothermia, with severe reversible respiratory failure (RRF), and treatment of other critical states leading to heart failure such as sudden cardiac arrest, cardiogenic shock or acute intoxication. Finally, it promotes donation after circulatory death (DCD) strategy in selected organ donor cases. ECMO enables recovery of organs' function after unsuccessful lifesaving treatment. Because this organizational model is complex and expensive, we use advanced high‐fidelity medical simulation to prepare for real‐life implementation. During the first four months, we performed scenarios mimicking "ECMO for DCD, " "ECMO for ECPR (extended cardiopulmonary resuscitation), " "ECMO for RRF" and "ECMO in hypothermia." It helped to create algorithms for aforementioned program arms. In the following months, three ECMO courses for five departments in Poznan (capitol city of Greater Poland) were organized and standardized operating procedures for road ECMO transportation within Medical Emergency System were created. Soon after simulation program, 38 procedures with ECMO perfusion therapy including five road transportations on ECMO were performed. The Maastricht category II DCD procedures were done four times on real patients and in two cases double successful kidney transplantations were carried out for the first time in Poland. ECMO was applied in two patients with hypothermia, nine adult patients with heart failure, and five with RRF, for the first time in the region. In the pediatric group, ECMO was applied in four patients with RRF and 14 with heart failure after cardiac surgery procedures. Additionally, one child was treated successfully following 200 km‐long road transport on ECMO. We achieved good and promising results especially in VV ECMO therapy. Simulation‐based training enabled us to build a successful procedural chain, and to eliminate errors at the stage of identification, notification, transportation, and providing ECMO perfusion therapy. We discovered the important role of medical simulation, not only to test the medical professional's skills, but also to promote ECMO therapy in patients with critical/life‐threatening states. Moreover, it also resulted in increase of the potential organ pool from DCD in the Greater Poland region.